Meningkatkan Semangat Mengonsumsi Jus Melalui Boba - Annisa Nurintha Fitri; Fahmi Mahmuddin Siregar; Lestari Bunga Pertiwi; Dini Safitri (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Boba is a bubble tea made from tapioca flour and has a sweet taste. However, not a few boba that uses sugar in excess which is very dangerous for human health. At the present time all things can be viral quickly, something new will quickly spread in the community. A thing that is trending in the community will affect one's desires. As is currently developing boba, but many boba is not good for health. Therefore, we want to create healthy boba made from natural ingredients that can maintain health. Boba is different from boba in general. Fruit juice mixture that will add properties for health and fitness. We use Instagram social media to make observations and dedication even though in the midst of the 19th outbreak of Covid this service will continue.